Inflation and unemployment interdependance: Evidence from the Western Balkan countries - Jelena Dimovski; Gabrijela Mitić; Milan Veselinović (Economic Themes, 2023)
The discussion over the relationship between the inflation, unemployment and economic growth has been relevant over the centuries to a wide range of economic interests. It is agreed among the researchers and economists that reaching the price stability, ceteris paribus, will have a beneficial effect on employment and economic prosperity measured with GDP growth, particularly under the assumption of identifying and maintaining an optimum sill. However, as achieving the ideal deal is quite challenging to the monetary authorities and the unemployment keeps to be one of the main obstacles across the globe, particularly for emerging economies, assessing the relationship among these variables remains in the focus of economic audience. Thus, the aim of this study is to examine the interdependence between the inflation, unemployment and economic growth through an empirical assessment of the inverse relationship between the first two and testing the validity of the Okun's law for the sample of the Western Balkan (WB) countries and the European Union as a whole. For this purpose, the panel data available on the World Bank platforms for the time period from 2006 to 2021 were used. In addition, aiming to assess the contribution of unemployment and inflation to GDP growth, the regression analysis was performed based on the standard model. The findings of this research confirm the trade-off between inflation and unemployment for all examined countries (Serbia, B&H, Montenegro, Albania) and the EU, except for North Macedonia. Differently, mixed results were obtained considering the Okun's law. While some results confirm the validity of this law, other disprove it. The results of the regression analysis for all countries show that a rise in inflation and drop in unemployment positively contribute to the countries' GDP growth.
Keywords: E60; O11; O4; 330; inflation; unemployment; interdependence; trade-off; Western Balkans; EU